Assessment of Appropriate Doses of GA3 and Row Ratio for Better Seed Yield of a Promising Hybrid Rice Variety (Bangladesh Rice Journal, 2015)
A field experiment was carried out at the Bangladesh Rice Research Institute (BRRI) farm, Gazipur during dry season 2013-14 to find out the appropriate GA3 dose and row ratio for hybrid seed production. GA3 doses were applied @ 0, 80, 160, 240 and 320 g ha-1 with different row ratio. Results revealed that GA3 application influenced the panicle exsertion rate only. The calculated optimum GA3 dose was 302.4 g ha-1 with the highest PER (84.62%). Seed yield and OCR were influenced by row ratio. The highest OCR was observed with 2:12 row ratio while the highest seed yield was found in 2:14 row ratio.Bangladesh Rice j. 2015, 19(1): 57-61